2007
DOI: 10.4269/ajtmh.2007.77.812
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of B. Pseudomallei in Clinical Samples

Abstract: We undertook a prospective study to quantitate Burkholderia pseudomallei in blood, urine, respiratory secretions, and pus [corrected] obtained from 414 patients with melioidosis. The median was count 1.1, 1.5 x 10(4), 1.1 x 10(5), and 1.1 x 10(7) CFU/mL in these sample types, respectively. This provides important insights into the likely feasibility of future studies such as expression microarray analysis using clinical material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 11 publications
6
46
0
Order By: Relevance
“…pseudomallei from blood cultures from two septicemic patients in Australia [29]. The simulated blood culture experiment in which 10 CFU was used as the starting inoculum reflects the bacterial load in blood during human infection, which has been reported previously to be a median count of 1.1 CFU/ml [48]. Our observation that identification of B .…”
Section: Discussionmentioning
confidence: 99%
“…pseudomallei from blood cultures from two septicemic patients in Australia [29]. The simulated blood culture experiment in which 10 CFU was used as the starting inoculum reflects the bacterial load in blood during human infection, which has been reported previously to be a median count of 1.1 CFU/ml [48]. Our observation that identification of B .…”
Section: Discussionmentioning
confidence: 99%
“…Culture is routinely performed on multiple sample types (blood, urine, pus, sputum, etc.) and isolation of B. pseudomallei from any one of these cultures is diagnostic for melioidosis [5], [6]. However, recent modeling data has confirmed that culturing is an imperfect gold standard [7].…”
Section: Introductionmentioning
confidence: 99%
“…Methods that achieve this detection include polymerase chain reaction (PCR), loop-mediated isothermal amplification (LAMP), and antibody-based immunofluorescence (IFA), which can be applied to a range of sample types, including sputum, pus, urine, respiratory secretion, and body fluids 36. Around one-half of patients with melioidosis have positive blood cultures,7 and an important drawback for all antigen assays is that the median B. pseudomallei count in blood is 1 cfu/mL,8 which is far below the achievable level of detection by the IFA. Pre-incubation of blood cultures would be predicted to increase the sensitivity of IFA, and despite this extra step would still reduce the time to diagnosis compared with conventional culture and biochemical identification.…”
mentioning
confidence: 99%